Gender equality in agrifood systems: Indicator list (GEASIL) - Mora, Catalina; Morgan, Miranda; Elias, Marlene (2023)
The Gender Equality in Agrifood Systems: Indicator List (GEASIL) is aimed at stakeholders who strive to address gender inequalities in value chains and require effective gender-responsive monitoring systems to track progress and guide decision-making. It is a consolidated list of nearly 400 illustrative indicators, selected and curated from over 1,500 original indicators identified in a scoping review. The list of indicators is not exhaustive and can be used in combination with other searchable indicator databases. It is intended to serve as a starting point and inspiration for exploring a variety of gender equality-related changes, drawing on existing measures from gender-responsive interventions and corresponding monitoring systems.